2022
DOI: 10.1055/s-0042-1757353
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Systemic Immune-Inflammation Index in Newborns with Urinary Tract Infection

Abstract: Objective Aim of this study is to investigate the diagnostic role of the systemic immune-inflammation index (SII; neutrophil × platelet [PLT]/lymphocyte) in the prediction of renal involvement in newborns with urinary tract infection (UTI). Study Design We conducted a retrospective cohort study among 117 newborns with a gestational age greater than 35 weeks and hospitalized in the NICU. Laboratory values obtained from blood samples taken before the initiation of antibiotics were evaluated for renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…Karakaya et al assessed the role of CBC-derived parameters in predicting acute pyelonephritis and showed that SII was among the best predictors of the development of acute pyelonephritis [28]. Likewise, according to Kocaaslan et al, SII might have a predictive value toward renal involvement in newborns with urinary tract infections [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakaya et al assessed the role of CBC-derived parameters in predicting acute pyelonephritis and showed that SII was among the best predictors of the development of acute pyelonephritis [28]. Likewise, according to Kocaaslan et al, SII might have a predictive value toward renal involvement in newborns with urinary tract infections [29].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies have focused on the systemic immune inflammation index (SII), a newly defined ratio combining neutrophil, lymphocyte, and platelet counts. It is suggested as a prognostic indicator, comprehensively reflecting the inflammatory and immune status of patients with various renal diseases [25][26][27][28][29][30][31][32][33]. The data on SII in adults with CKD are limited, though elevated SII seems to have a predictive value for mortality risk among pre-dialysis and hemodialysis adult patients [30,31].…”
Section: Introductionmentioning
confidence: 99%